BIOREMEDIASI Pb OLEH BAKTERI INDIGEN LIMBAH CAIR AGAR - Senja Ikerismawati (Jurnal Biosilampari : Jurnal Biologi, 2019)
Bacteria isolated from ad environment contaminated with heavy metals are very potential as heavy metal bioremediation agents called indigenous bacteria. The purpose of this study was to isolate and identify indigenic bacteria that have the potential as Pb bioremediation agents in agar liquid waste and to analyze the ability of indigenic bacteria in reducing Pb. The research design used Completely Randomized Design (RAL) two factorial with variation of bacteria and eight days of treatment. Data were analyzed using two-way ANOVA with Duncan's advanced test. The results showed that there were eight isolates resulting from the isolation of agar liquid waste. The isolates of liquid waste indigen bacteria so that the most potential in reducing Pb were isolated H, E and F. The three isolates were able to reduce Pb in sterile agar liquid waste by 82.6%, 81.3% and 79.3% for eight days of treatment. The identification results using Microbact TM GNB 12A / B / E, 24 Identification Kits showed that H bacterial isolates were Bacillus alvei, E isolates were Bacillus pumilus species and F isolates were Bacillus lichenformis species